Public health advocacy in action: the case of unproven breast cancer screening in Australia - Johnson, R.; Croager, E.; Kameron, C.; Pratt, Steve; Vreugdenburg, T.; Slevin, Terry (2016)
In recent years, nonmammographic breast imaging devices, such as thermography, electrical impedance scanning and elastography, have been promoted directly to consumers, which has captured the attention of governments, researchers and health organisations. These devices are not supported by evidence and risk undermining existing mammographic breast cancer screening services. During a 5-year period, Cancer Council Western Australia (CCWA) used strategic research combined with legal, policy and media advocacy to contest claims that these devices were proven alternatives to mammography for breast cancer screening. The campaign was successful because it had input from people with public health, academic, clinical and legal backgrounds, and took advantage of existing legal and regulatory avenues. CCWA's experience provides a useful advocacy model for public health practitioners who are concerned about unsafe consumer products, unproven medical devices, and misleading health information and advertising.